Effects of tussah immunoreactive substances on growth, immunity, disease resistance against Vibrio splendidus and gut microbiota profile of Apostichopus japonicus. Issue 63 (April 2017) - Ma, Shuhui; Sun, Yongxin; Wang, Fuqiang; Mi, Rui; Wen, Zhixin; Li, Xuejun; Meng, Nan; Li, Yajie; Du, Xingfan; Li, Shuying
Abstract: Tussah immunoreactive substance (TIS) comprises a number of active chemicals with various bioactivities. The current study investigated the effects of these substances on the sea cucumber Apostichopus japonicus . The specific growth rate (SGR) of TIS-fed sea cucumbers was significantly enhanced, whereas no significant difference in SGR was observed between those soaked in antibiotics and those fed with basal diet only. TIS also improved the immune response of the animals when given at a dose of 1.0% or 2.0%, as shown by increased phagocytic, lysozyme, superoxide dismutase, alkaline phosphatase, acid phosphatase, and catalase activities following injection with live Vibrio splendidus . At a dose of 1.0% or 2.0%, TIS significantly enhanced the immune ability ( P  < 0.05) of the sea cucumbers, but except for lysozyme activity, other immune indices were reduced one day after the animals were injected with Vibrio splendidus . However, the values of these immune indexes were still significantly higher compared to those of the control groups ( P  < 0.05). Intestinal micro flora counts and high-throughput sequencing showed that dietary TIS could improve the amount of probiotic bacteria, yielding a 6-fold increase in Bacillus and 10-fold increase in Lactobacillus for sea cucumbers fed with 2.0% TIS diet compared to the control. Furthermore, TIS-containing diet also greatly reduced the number of harmful bacteria, with the number of Vibrio in sea cucumbers fed with 1%TIS diet decreased by 67% compared to the control. The results thus indicated that TIS increased the growth of sea cucumbers and enhanced their resistance to V. splendidus infection by improving the immunity of the animals. TIS also improved the gut microbiota profiles of the animals by increasing the probiotics and reducing the harmful bacteria within their guts. Highlights: Dietary TIS can significantly improve resistance to diseases by enhancing immunity of the sea cucumbers. TIS can improve the gut microbiota profiles of the sea cucumbers. TIS was as effective as (if not better than) antiobiotics in term of protecting sea cucumbers against bacterial infection.